Evaluating the effects of Zn(II) on high-rate biogranule-based denitrification: Performance, microbial community and sludge characteristics. (May 2019) - Cheng, Ya-Fei; Li, Gui-Feng; Liu, Ying-Yi; Zhu, Bing-Qian; Zhang, Qian; Xue, Yuan; Zhang, Zheng-Zhe; Jin, Ren-Cun
Graphical abstract: Highlights: The suppression threshold of Zn(II) on reactor performance was 10 mg L −1 for long-term exposure. Castellaniella mainly was devoted to denitrification under no or low Zn(II) stress conditions. Klebsiella was the dominant denitrifying bacteria under high Zn(II) stress conditions. Abstract: High-rate denitrification is a popular and efficient process for treatment of nitrate-rich wastewater. Knowing the effect of heavy metals on denitrification is essential for industrial development. In the present study, the long-term impacts of Zn(II) on denitrifying granular sludge were investigated. The suppression threshold of Zn(II) on denitrifying bacteria was 10 mg L −1 for long-term exposure. The nitrogen removal rate was decreased by long-term addition of 10 mg L −1 Zn(II). Castellaniella and Klebsiella were the two dominant genera under Zn(II) stress. The relative abundance of Klebsiella sharply decreased to 4.64% after the addition of 10 mg L −1 Zn(II), whereas Castellaniella was susceptible to 2 mg L −1 Zn(II), revealing that Castellaniella mainly was devoted to denitrification under no or low Zn(II) stress conditions, whereas Klebsiella was effective under high Zn(II) stress.